Performance of elephant grass and elephant grass x pearl millet hybrids in the semi-arid region of northeast Brazil - dos Santos, Maria do Carmo Santana; Tabosa, José Nildo; Dias, Flávio Marcos; de Feitas, Erinaldo Viana; Lira, Mário de Andrade (Pesquisa Agropecuaria Brasileira, 1994)
This experiment was carried out to evaluate 41 clones of elephant grass (Pennisetum purpureum Schum.) and elephant grass x pearl millet (Pennisetum americanum (L.) Leeke) hybrids for the following parameters: dry matter yield, plant height and leaf/stem ratio. The experiment was conducted in the experimental station of Arcoverde-IPA, located in the Semi-Arid, region of Northeast Brazil, during the years of 1986 and 1987. The experimental design used was randomized blocks. Dry matter yield varied from 16.0 to 18.8 t/ha, for the Itapemirim and Taiwan A-144 clones respectively (selected material). Plant height ranged from 146 to 236 cm for the 41 clones evaluated. Leaf/stem ratio varied from 0.40 to 0.81. Dry matter yield was significant and positively correlated with plant height.